In-depth profiling, nontargeted metabolomic and selective ion monitoring of eight chemical markers for simultaneous identification of different part of Eucommia ulmoides in 12 commercial products by UPLC/QDa. (1st November 2022) - Liu, Xing; Zhang, Jianqing; Li, Yun; Yao, Changliang; An, Yaling; Wei, Wenlong; Yao, Shuai; Yang, Lin; Huang, Yong; Qu, Hua; Guo, De-an
Highlights: 222 compounds were tentatively characterized from the bark, leaf, flower, seed of Eucommia ulmoides . A systematic comparison among the bark, leaf, flower, seed of E. ulmoides was firstly conducted. 8 compounds were found to be the most important chemical markers to discriminate four parts of E. ulmoides . An UPLC/QDa-SIM method was established and successfully applied to precisely identify four parts of E. ulmoides from 12 different commercial products. Abstract: Despite Eucommia ulmoides to be served as a crucial source for food additives and healthcare products, unclarity of the metabolomic differences among four different plant parts (bark, leaf, flower, seed) seriously restricts the comprehensive quality control of the herb and its related commercial products. In this study, a strategy integrating in-depth profiling, nontargeted metabolomics, and selected detection was established and exemplarily applied to authenticate E. ulmoides related products. UPLC/Q-TOF Fast DDA approach was utilized for in-depth profiling among four parts to characterize 222 compounds. In addition, 38 batches of different parts of E. ulmoides were compared by metabolomics method, and multi-step chemometrics analysis to unveil 25 chemical markers. Finally, an UPLC/QDa-SIM method was established based 8 most important diagnosis components to identify 12 commercial products. This study provides a novel and comprehensive strategy for the quality assessment of foods and dietary supplements.